Feminist Consciousness to Prevent Marital Rape Victimization of Women during the Covid-19 Pandemic - Jenny Rahayu Afsebel Situmorang (UIN Raden Mas Said Surakarta, 2021)
Marital rape is one of the sexual violence against women (wives). The study's focus was to analyze the relationship between rape in marriage and women's awareness during the Covid-19 pandemic. The research method uses library research that is representative and relevant to the research object. Regarding the feminist consciousness, many women do not realize that women end up helpless and fight when they are not good, including experiencing marital rape. The problem is the case not recorded, and the victim does not receive protection and their rights. The feminist consciousness of women can open women's eyes that there is sexual violence against women through marital rape. Furthermore, women can be aware of these cases, especially so as not to experience the same thing, especially during the Covid-19 pandemic. Then, women are empowered and protected from marital rape.